2010
DOI: 10.1093/aje/kwq029
|View full text |Cite
|
Sign up to set email alerts
|

Night-Shift Work and Breast Cancer Risk in a Cohort of Chinese Women

Abstract: Shift work involving disruption of circadian rhythms has been classified as a probable cause of human cancer by the International Agency for Research on Cancer, based on limited epidemiologic evidence and abundant experimental evidence. The authors investigated this association in a population-based prospective cohort study of Chinese women. At baseline (1996-2000), information on lifetime occupational history was obtained from 73,049 women. Lifetime night-shift exposure indices were created using a job exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 19 publications
10
98
2
4
Order By: Relevance
“…Although a few studies reported no significant association between breast cancer and night work (O'Leary et al 2006, Pronk et al 2010, the majority of recent studies reported significant or borderline associations, with the strongest association found with long-term exposure to night work (Hansen 2001, Schernhammer et al 2001, Hansen & Lassen 2012, Hansen & Stevens 2012, Knutsson et al 2013, Menegaux et al 2013, Rabstein et al 2013, Akerstedt et al 2015, Papantoniou et al 2015. Meta-analysis studies have also reported a positive association between night work and breast cancer risk (Jia et al 2013) and that a positive dose-response gradient is observed for breast cancer with increased years of night shift and cumulative night work .…”
Section: Nuclear Receptors In Breast Cancermentioning
confidence: 99%
“…Although a few studies reported no significant association between breast cancer and night work (O'Leary et al 2006, Pronk et al 2010, the majority of recent studies reported significant or borderline associations, with the strongest association found with long-term exposure to night work (Hansen 2001, Schernhammer et al 2001, Hansen & Lassen 2012, Hansen & Stevens 2012, Knutsson et al 2013, Menegaux et al 2013, Rabstein et al 2013, Akerstedt et al 2015, Papantoniou et al 2015. Meta-analysis studies have also reported a positive association between night work and breast cancer risk (Jia et al 2013) and that a positive dose-response gradient is observed for breast cancer with increased years of night shift and cumulative night work .…”
Section: Nuclear Receptors In Breast Cancermentioning
confidence: 99%
“…FĂŒr Brustkrebsrisiken von Krankenschwestern liegen etwas besser kontrollierte Studien vor (Schernhammer et al 2006). Doch auch hier werden signifikante kausale ZusammenhĂ€nge bestritten (Kolstad et al 2010;Pesch et al 2010;Pronk et al 2010). Da Krebserkrankungen im vorliegenden Datensatz nicht enthalten sind und darĂŒber hinaus Langfristfolgen nicht untersucht werden können, mĂŒssen sie in dieser Untersuchung unberĂŒck-sichtigt bleiben.…”
Section: Problemstellung Und Forschungsstandunclassified
“…This database contains a continuously updated set of information on the subjects of national economy, with the activities of the enterprises encoded according to the Polish Classification of Activities (Polska Klasyfikacja DziaƂalnoƛci -PKD) further studies was expressed as follows: "more studies are needed to examine this potential risk in other professions and for other cancers" (Dr Cogliano, Head of the IARC Monographs Programme) [2,3]. Over the past 5 years, eight additional epidemiological studies have been reported, including: three investigations in nurses: a Norwegian nested case-control study on breast cancer [4], a Danish nested case-control study on breast cancer [5], an ovarian cancer in Nurses Health Study [6], as well as a breast cancer case-control study in Germany [7], and France -breast cancer case-control CECILE study [8], industrial males cohort in Japan -a study on prostate cancer [9], and females in China -a study on breast cancer [10]. Moreover, one registry-based linkage study was conducted in Scandinavian countries [11].…”
Section: Methodsmentioning
confidence: 99%